MAMMALIAN GLYCANS AS MODULATOR OF INFLAMMATORY RESPONSES - Maheswara Reddy Mallu; Siva Reddy Golamari; Sandeep Vemula; Srinivasa Reddy Ronda (International Journal of Pharma and Bio Sciences, 2016)
In the perspective of the genetic code, a new concept for coding information is emerging: the sugar code. This describes glycans as a third class of bio-informative macromolecules, next to nucleic acids and proteins. As a first step, the complexity of all glycans being produced in an organism, the glycome is being identified. In the past, the lack of possibilities to analyze glycan chains in detail was a main reason why scientists did not pay adequate attention to the potential information-encoding system hidden in sugar structures. Today, sophisticated analytical procedures are at hand and thus these problems have been elegantly mastered. Glycan, a unique member of the growing family of β-galactoside binding lectins, contains a single carbohydrate recognition domain and a glycine rich N-terminal domain, through which it can form oligomers and functions to cross-link both carbohydrate and non-carbohydrate ligands. Glycans are widely expressed in adult tissues, particularly on and secreted by activated macrophages, monocytes and adipocytes. Glycans have been implicated in many facets of the inflammatory response including neutrophil and macrophage activation and function.